#### Answer

There is no solution for this equation.
In set notation this is shown by the empty set: { }

#### Work Step by Step

4(x + 2) + 1 = 7x - 3(x - 2)
To solve this equation, we first need to apply the distributive property to both the right and left side of the equation.
4x + 8 + 1 = 7x - 3x + 6
Now, combine the like terms on each side of the equation.
4x + 9 = 4x + 6
Next, subtract 4x from both sides of the equation.
4x - 4x + 9 = 4x - 4x + 6
and we get: 9 = 6
Since there is no way that 9 = 6, we say that the equation has no solution...or the solution is the empty set.